The esperanza window trap reduces the human biting rate of Simulium ochraceum s.l. in formerly onchocerciasis endemic foci in Southern Mexico - Rodríguez Pérez, Mario Alberto; Garza Hernandez, Javier Alfonso; Salinas Carmona, Mario César; Fernández Salas, Ildefonso; Reyes Villanueva, Filiberto; Real Najarro, Olga; Cupp, Eddie W.; Unnasch, Thomas R. (Public Library of Science, 2017)
Abstract Background The Esperanza Window Trap (EWT) baited with CO2 and human sweat compounds is attractive to Simulium ochraceum s.l., the primary vector of Onchocerca volvulus in the historically largest endemic foci in Me ´xico and Guatemala. Methodology/Principal findings The ability of the EWT to locally reduce numbers of questing S. ochraceum s.l. was evaluated in two formerly onchocerciasis endemic communities in Southern Me ´xico. At each community, two EWTs were placed in or near a school or household and flies were collected sequentially for a total of 10 days. Black fly collections were then carried out for an additional 10 days in the absence of the EWTs. Flies were also collected outside the dwellings to control for variations in the local fly populations. When the EWTs were present, there was a significant reduction in the human biting rate at both the household and school locations at collection sites, with a greater effect observed in the schools. Conclusions/Significance These results indicate that the EWTs not only have potential as a black fly monitoring tool but may be used for reducing personal exposure to fly bites in Mesoamerica. Author summary The Esperanza window trap (EWT), when used in large numbers (3-4/household and >90% coverage) and baited with human sweat compounds and CO2, can be used to collect epidemiologically significant numbers ofSimulium ochraceum s.l., the primary vector of Onchocercavolvulusin the historically largest endemic foci in Me ´xico and Guatemala. In the present study, we evaluated the ability of the EWT to reduce the personal biting rate by questingS.ochraceum s.l. in two formerly onchocerciasis endemic communities in Southern Me ´xico. At each community, two EWTs were placed in or near a school or household and flies were collected sequentially for a total of 10 days. Black fly collections were then carried out for an additional 10 days in the absence of the EWTs. When the EWTs were present, there was a significant reduction in the human biting rate at each of the four collection sites, varying from 14% to 51%. This study demonstrates that the EWTs have potential both as a black fly monitoring and personal exposure reduction tool in Mesoamerica.